Gênes pour mémoire - Alice Leroy; Carlo Augusto Bachschmidt (Laboratoire Italien)
In August 2022, Carlo Augusto Bachschmidt, filmmaker and activist, attended the “États généraux du film documentaire” in Lussas, Ardèche (France), to present the archive he had helped to build within the Genoa Legal Forum, a coordination group set up in the wake of the Genoa Social Forum to support civil proceedings and lawyers in the long run after the 2001 counter-summit. In order to initiate a debate on the judicial and memorial stakes involved in using this archive, he brought with him two of his films: OP Genova (2007), made during the proceedings and based on archived audiovisual material, and Black Block (2011), made with some of the victims of the police raid on the Diaz school during the night of 21 July 2001. This discussion with the festival audience provided an opportunity to look back at the creation of this archive, which is unprecedented in its scope and diversity of formats – documentaries, militant videos, local television rushes and audio recordings of police radio communications– and also at the editing and reconstitutions to which it has given rise, not only in the context of the trials in which these materials were shown, but also beyond the judicial arena, in the militant worlds and more broadly in the constitution of a record of the event. The project of this archive and its uses can therefore be understood as an undertaking not of institutionalisation but of critical rereading of material: collecting and preserving, yes, but dedicated to an ambition that is irreconcilable with the framework of political and judicial institutions. What are the historiographical and critical issues involved in such an approach? Who is it for? What resonance does it have with other narratives of past and present violence?